Composite glass ceramics - a promising material for aviation - Дмитрієв, М. В.; Лєнков, С. В. (Proceedings of National Aviation University (archive), 2000)
The analysis of the technical and technological characteristics of the composite ceramic as a material for electrical and structural parts in aircraft. The economic and technological advantages compared to ceramic pottery and proposed options for development of production in Ukraine